Assessing Measurement Invariance in Cross‐National Consumer Research - Steenkamp, Jan‐Benedict E. M.; Baumgartner, Hans (Journal of Consumer Research, 1998)
Assessing the applicability of frameworks developed in one country to other countries is an important step in establishing the generalizability of consumer behavior theories. In order for such comparisons to be meaningful, however, the instruments used to measure the theoretical constructs of interest have to exhibit adequate cross-national equivalence. We review the various forms of measurement invariance that have been proposed in the literature, organize them into a coherent conceptual framework that ties different requirements of measure equivalence to the goals of the research, and propose a practical, sequential testing procedure for assessing measurement invariance in cross-national consumer research. The approach is based on multisample confirmatory factor analysis and clarifies under what conditions meaningful comparisons of construct conceptualizations, construct means, and relationships between constructs are possible. An empirical application dealing with the single-factor construct of consumer ethnocentrism in Belgium, Great Britain, and Greece is provided to illustrate the procedure.